2009
DOI: 10.1007/s00441-009-0902-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the actin-associated protein transgelin (SM22) is decreased in prostate cancer

Abstract: Transgelin is an actin-binding protein shown to be tumour-suppressive. Loss of transgelin expression in transformed cells is associated with oncogenesis. This study aimed to determine whether transgelin expression was suppressed in prostate cancer. An in silico meta-analysis with public-domain expressed-sequence-tag libraries of normal human prostate epithelium, prostatic intraepithelial neoplasia, invasive carcinoma and metastasised lesions predicted decreased transgelin expression with disease progression. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…5C and D; refs. [36][37][38][39][40][41][42]. These observations therefore provide a mechanism for decreased motility, which corresponds well to the observed phenotype and the expected role of the Mediator complex.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…5C and D; refs. [36][37][38][39][40][41][42]. These observations therefore provide a mechanism for decreased motility, which corresponds well to the observed phenotype and the expected role of the Mediator complex.…”
Section: Discussionmentioning
confidence: 55%
“…To systematically investigate the mechanism of action, senexin A-treated DU-145 cells were subjected to RNA sequencing. Among the genes most strongly upregulated, several have previously been implicated in reduced migration of cancer cells or as being repressed during prostate cancer progression such as such as TAGLN (36,37), CDH1 (38, 39), CDH3 (40), TPM1 (41), or MYL-9 (refs. 39, 42; Fig.…”
Section: à8mentioning
confidence: 99%
“…The second dataset (GDS2547) (24) compared normal prostate specimens without any pathology, normal prostate adjacent to tumor, primary prostate tumor, and metastatic prostate cancer. Relative levels of expression of Lin28, AR, and Myc were determined by comparison of single channel counts and expressed as a percentage of the highest count in the data set (25). Significant differences between groups were determined by Microsoft Excel Tools.…”
Section: Methodsmentioning
confidence: 99%
“…It is known, that transgelins are actin-associated proteins that participate in cytoskeleton formation [42]. Accordingly, the expression changes of transgelin genes (TAGLN, TAGLN2) during cancerogenesis can have an influence on cell motility, and also on invasiveness and Table 1).…”
Section: Comparative Analysis Of Protein Fractionsmentioning
confidence: 99%
“…However the data concerning the character of expression changes of transgelin genes at prostate cancer are conflicting. So, Prasad et al [42] have recently reported that transgelin level is decreased in various types of prostate cancer cultured cells (except Du-145), and Lee et al [43] have the opposite observations that level of transgelin is essentially increased in malignant prostate cells.…”
Section: Comparative Analysis Of Protein Fractionsmentioning
confidence: 99%